PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STRUCTURED NUMBERED HEADS (SNH) TERHADAP HASIL BELAJAR MATEMATIKASISWA KELAS IX SMP NEGERI 1 RAMBAH SAMO - -, Faridah; -, Hardianto; -, Nurrahmawati (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2015)
The purpose of this research was to know the effect ofstructured Numbered Heads (SNH)on the results of mathematics students ofgrade IX students of Junior High School Negeri 1 Rambah Samo. Sample was collected by simple random sampling cooperative learning model whith simple random sampling technique. The hypothesis test used t-test, with the result was 2.1143> 1.9944 for Î± = 0.05. Because t count> t table, H0 is rejected. Then there was effect of the experimentation of Structured Numbered Heads (SNH) cooperative learning model on the results of mathematics students of grade IX was students of Junior High School Negeri 1 Rambah Samo